Design & Development of a Robotic System Using LEGO Mindstorm - Abd Manap, Nurulfajar; Md Salim, Sani Irwan; Haron, Nor Zaidi (2006)
This research presents a design and development of robotic system based on LEGO Mindstorm kit. The system is capable in operating an off-line programming method, starting from its programming sequences until robotic implementation of the program. During early stages, the research is emphasis more towards designing a robotic system using RoboLab software and C++ programming language. A robotic hardware system has been developed using LEGO Mindstorm kit. The robotic model acts as a prototype or test-bed for programming execution. The model involves motorize movement, sensors detection and machine vision to be manipulated by the programmers inside their programs. Since the model is built using LEGO bricks, the model is fully customized, in term of its applications, to perform any relevant tasks. Ultimately, the algorithm development program designed earlier is linked up directly to the robotic model for program implementation and verification. For this research, several set of robots by using Lego has been developed and it uses LeJos and C programming techniques as a platform. A Java-based robot development tool has been set up as alternative programming methods incorporating LeJos and the controller. A prototype of a mobile robot based on Lego successfully implemented by using PIC and can be controlled through voice recognition.